An admirer of Dante in the 18th century, Agostino Paradisi the Younger - Venturelli, Piero (Montesquieu.it, 2021)
This paper focuses on an important 18th Century admirer of Dante Alighieri, Agostino Paradisi the Younger. In 1758, at only twenty-two years of age, Paradisi published an inspired ode in defense of the Comedy so to highlight Dante’s ability to write in a masterly way regarding the divine mysteries, to investigate the depth of the human soul and to draw memorable images. Paradisi composed his poem, entitled Contra the Author of the Pseudo-Virgilian Letters to Lord Canon Ritorni, in reaction to the anonymous publication of the Ten Letters of Virgil (1757) by Saverio Bettinelli. The latter criticized, in these epistles, the Italian poetic tradition and above all the Comedy, a work he accused of obscurity, extravagance, deformity, and tediousness. For the rest of his life Paradisi would continue to praise Dante. This article ends with the full text of the apologetic ode written by Paradisi.